Establishing a Faculty Mentoring Program - Joshua Schulte (Academic Chairpersons Conference Proceedings, 2022)
Presenter will discuss the establishment and conductance of a college-wide faculty mentoring program. The program entails connecting a new faculty member with a mentor and includes regular meetings, observations, and discussions of pedagogy.
Keywords: mentoring; faculty; collegiality; college culture; leadership